Measuring the global shadow economy : the prevalence of informal work and labour - Williams, Colin C. (Edward Elgar Publishing, 2016)
"This book brings together two leading researchers in the field to provide a comprehensive overview of the shadow economy from a global perspective. Reviewing the advantages and disadvantages of different ways of measuring the informal sector, the authors evaluate its size and key determinants across the world. Williams and Schneider clearly establish the persistence and prevalence of the shadow economy, analysing the narrowness of existing policy approaches and explaining how these fail to address the key factors for its existence and may even exacerbate the problem. Proposing an alternative way forward, the authors argue that little headway will ever be made in reducing the shadow economy until there are changes not only to the character of formal institutions but also informal institutions (the values, beliefs and norms of citizens) through the introduction of macro-level structural changes. This timely, cutting-edge review of the global shadow economy and how it can be measured and tackled is an invaluable resource for postgraduate students, researchers and policy-makers, particularly those with a interest in tax evasion and informal labour."--Page 4 of cover.